Answer:
180 students
Step-by-step explanation:
Answer:
x-6=y
6x= 8+4y
Step-by-step explanation:
We have that
x²<span>-6x+7=0
</span>Group terms that contain the same variable
(x²-6x)+7=0
Complete the square Remember to balance the equation
(x²-6x+9-9)+7=0
Rewrite as perfect squares
(x-3)²+7-9=0
(x-3)²-2=0
(x-3)²=2
(x-3)=(+/-)√2
x=(+/-)√2+3
the solutions are
x=√2+3
x=-√2+3
X=the number we have to find.
This expression "2(x+9)" is when the sum of a number and nine is doubled.
If the result is seven less than the number, we will have: x-7
We can suggest the following equation:
2(x+9)=(x-7)
2x+18=x-7
2x-x=-7-18
x=-25
answer: the number would be: -25.
The slope is 2 and the intercept is -3